Bibliographic and printing activities of the central library of the Academy of Sciences Lit. SSR in 1946-1985 - Adolfas Ivaškevičius (Knygotyra)
In the post-war period, alongside completing and cataloging, bibliographic service was organized in the Central Library of the Academy of Sciences of the Lithuanian SSR.